Kajian Aspek Biologi Stegobium paniceum (Coleoptera: Anobiidae) - V. Poerdriesti; F. X. Wagiman; Koeswari Ananda (Jurnal Perlindungan Tanaman Indonesia, 1998)
The biological aspects of Stegobium paniceum (L.) (Coleoptera: Anobiidae) was studied by culturing the insect on coriander seeds at the Laboratory of Research Center for Biological Control (RCBC), Gadjah Mada University, under room temperature of 26.55± 0.72oC – 30.66± 0.40oC and 57.38 ± 5.53% relative humidity. The results showed that egg, larval, and pupal stages of S. paniceum were 9.15±1.37; 35.97±5.53 and 5.80±0.54 days, respectively. Females laid eggs firstly at 5 days old, hence, the life cycle was 55.92 days. The female produced eggs for 4.69±3.42 days, as many as 13.67±9.39 eggs. The eggs were laid in the coriander seeds; up to more than 50 eggs per seed, but only 68.54±29.27% out of them hatched and the one to three individuals of them developed into adult. Larvae and pupae lived in the coriander seeds or in coriander powder. The adults did not eat and could survive for 27.90±18.71 days, but could cause damage by making exit holes on the coriander seeds. The pest might cause coriander damage up to 80%.